(untitled) (Elkom: Jurnal Elektronika dan Komputer, 2026)
This study aims to develop an Internet of Things (IoT)-based monitoring and automatic watering system for cactus ornamental plants to improve accuracy and efficiency in plant care. The problem addressed is the conventional watering method that relies on time intervals without considering actual soil moisture conditions, which may lead to overwatering or underwatering. The research method used is Research and Development (R&D), involving system design, implementation, and testing. The system integrates Arduino Uno as a microcontroller, soil moisture sensor to detect soil humidity, DHT11 sensor to measure temperature and air humidity, and Wemos D1 Mini for internet connectivity. Data from sensors are processed and transmitted to a Firebase real-time database, then displayed on a web interface for remote monitoring and control. The system is designed to automatically activate the water pump when soil moisture is below a predefined threshold and deactivate it when optimal conditions are reached. The results show that the system can monitor environmental parameters in real-time, provide stable sensor readings, and control irrigation effectively. The developed system improves watering efficiency, reduces human error, and ensures optimal growing conditions for cactus plants.